Perbedaan PERBEDAAN NILAI LEKOSIT ANTARA KOMPONEN DARAH PACKED RED CELLS (PRC) DAN PACKED RED CELLS LEUCODEPLETED (PRC-LD) DI UTD PMI KOTA SURABAYA TAHUN 2019 - Renata Primasari (Klinikal Sains : Jurnal Analis Kesehatan, 2021)
Abstract This leukodepleted PRC (PRC-LD) is considered capable of preventing reactions related to blood transfusions because it contains only a small number of leukocytes. The blood component of PRC-LD has also been shown to prevent or reduce transfusion reactions. Leukodepleted is a procedure to reduce the number of leukocytes in the blood or blood components to be transfused to a minimum of <1x106 leukocytes/unit (European standard) or reduce the number of leukocytes >99%. The purpose of this study was to see the difference in leukocyte values ​​in the PRC and PRC-LD components. The method used is analytic, namely research that aims to determine the relationship between variables within the scope of the laboratory. The method used is a comparative study. This study used 30 samples of PRC products and 30 samples of Leucodepleted PRC products at UTD PMI Surabaya City with 450 cc bags. The study was conducted in October - December 2019. The result was that the leukocyte value in the PRC blood component contained blood quality that did not meet the specifications as many as 30 bags (100%) had leukocyte levels >1x106 per bag. Meanwhile, the blood component of PRC-LD contains blood quality that meets the specifications as many as 30 bags (100%), having leukocyte levels <1x106 per bag. Conclusion The quality of PRC Leukodepleted blood component products, the quality of leukocyte levels that meet the specifications, there are 30 blood bags (100%). Keywords: Packed Red Cells Leukodepleted